Legal Strategies and Advocacy for Boosting Global Market Competitiveness of Geographical Indication Products in Temanggung - Waspiah, Waspiah; Rodiyah, Rodiyah; Afiatun, Umi; Baiquni, Muhammad Iqbal; Arifin, Ridwan; Putri, Nadiyah Meyliana; Damayanti, Fitria (Indonesian Journal of Advocacy and Legal Services, 2024)
Geographical Indication (GI) products hold significant potential for enhancing local economies and global market presence. However, GI products from Temanggung, Indonesia, face unique legal and competitive challenges that hinder their global competitiveness. This paper addresses the urgent need to bolster the international market position of Temanggung’s GI products through effective legal strategies and advocacy. The research is novel in its dual approach of combining legal analysis with strategic advocacy, focusing on a specific regional context that has received limited attention in existing literature. It examines the international and national legal frameworks affecting GI products, identifying gaps and proposing enhancements to strengthen legal protections and align with global standards. Additionally, the paper explores innovative advocacy methods to increase awareness and marketability, including strategic marketing, education, and stakeholder partnerships. The contribution of this research lies in its comprehensive analysis of both legal and advocacy dimensions, providing actionable recommendations for improving the competitiveness of Temanggung’s GI products. By addressing legal vulnerabilities and advocating for effective promotion, the paper offers a roadmap for policymakers, legal professionals, and local producers to enhance the global presence of Temanggung’s GI products. The findings aim to inspire similar strategies for other regions facing comparable challenges, ultimately contributing to the broader discourse on GI protection and market strategies. This research is crucial for addressing immediate challenges and leveraging the full potential of GI products in a competitive global marketplace.